Mixed malignant tumour of the lung. Issue 5 (October 1979) - Edwards, C W; Saunders, A M; Collins, F
Abstract : A mixed malignant tumour of the lung intermediate in type between pulmonary blastoma and carcinosarcoma is described. The epithelial component consisted of squamous carcinoma, undifferentiated carcinoma, and clefts lined by bland epithelial cells. The supporting stroma was composed of pleomorphic sarcoma, fibrosarcoma, chondrosarcoma, osteosarcoma, and indeterminate mesenchymal tissue. The tumour was removed surgically, but the patient died postoperatively with rapidly developing multiple bony and soft tissue metastases. Subcutaneous metastases showed the appearnce of poorly differentiated pleomorphic sarcoma. Published reports of mixed malignant lung tumours are reviewed.